From Lemmings in the Internet to New Valiant Protesters: Dysphemism shkolota and the representati on of adolescent participati on in the public sphere - I. V. Prus (Шаги, 2023)
In the late 2010s, one can observe intensification of debates about adolescents as political subjects among the various Russian media platforms. Adolescents became an object of close attention of political actors and institutions, journalists, pop artists and ordinary internet users. This process is very noticeable in the shifts of semantics of the dysphemism shkolota (originally a disparaging definition of elementary and middle school students). The article aims to give an overview of the change in the meaning of shkolota as the «commonplace» of imagination and representation of teenagers. To find out what shkolota means, I conducted an analysis of publications and comments on LiveJournal, a social media platform and the birthplace of shkolota. A symbolic path was traced from the «Lemmings in the Internet» to «New Valiant Protesters» within twelve years. In considering the semantic boundaries and the context of shkolota in publications and comments on the LiveJournal platform and correlating them with the socio-political context of Russia, I describe the process of transformation of the dysphemism as a simultaneous expansion of adolescent participation visibility in the public sphere and the deconstruction of the image of the passive, defenseless (primarily against adult manipulation) and dangerous adolescent in public rhetoric. Analysis of how shkolota was reshaped turns out to be a method that allows us to consider from a new perspective the public rhetoric about children in contemporary Russia.